UNILATERAL PROPTOSIS - A DIAGNOSTIC DILEMMA: Unilateral Proptosis - Yasin, Ubaid Ullah; Yaqub, Muhammad Amer; Naqvi, Syed Abid Hassan; Shahid, Muhammad; Habib, Asad; Awais, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To study epidemiology, presentation and management of cases with unilateral proptosis presenting at a tertiary care hospital.Study Design: Case series.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Jan 2016 to Dec 2017.Methodology: Retrospective analysis of hospital record of patients with unilateral proptosis was carried out. Data was entered and analyzed in SPSS version 22. Chi square test was used for statistical analysis.Results: Thirty-three cases of unilateral proptosis with a mean age of 41.79 ± 3.87 years were included in the study. Pain was the most common association. Proptosis was mild in 42.4%, moderate in 48.5% and severe in 9.1% cases. In 61% cases, diagnosis was made on excisional or incisional biopsy and on the basis of radio imaging in 39% cases. Most common cause of proptosis found was pleomorphic adenoma (12%). Patients with axial and non-axial proptosis were 48.5% and 51.5% respectively. Fourteen cases (42.5%) were managed surgically and 2 cases (6%) were observed. Total of 22 cases (67%) improved after treatment, 8 cases (24%) went into remission, 2 (6%) deteriorated, and 1 (3%) died in the study period.Conclusion: Unilateral proptosis is a diagnostic challenge. Pertinent history taking and detail examination is the key, but associated signs or symptoms not always point towards correct diagnosis. Tissue biopsy provides a conclusive diagnosis especially where radio imaging is doubtful.